Young children's fairness judgements on the distribution of rewards and responsibilities: allocation patterns and consistencies across two kinds of distribution. Issue 7 (7th June 2019) - Hashimoto, Yuko; Toda, Yuichi
ABSTRACT: The present study examined whether young children demonstrated consistencies in their allocation patterns across distributions of positive and negative resources. Preschool children from younger (age 4–5) and elder (age 5–6) classrooms were asked to allocate rewards when one person contributed more than the other and to allocate the responsibility of cleaning up the toys when only one person enjoyed the benefit of playing. By presenting two conditions for each distribution (the person who contributed more or enjoyed the benefit was the participant in one situation and the peer in the other), four allocation types (equity, equality, selfish, and generous) were identified. Children in both groups showed generous patterns in both distributions, but the differences for age were not significant. Despite more elder children applied the same rules to both distributions compared to the younger children, no age difference was found. These findings indicate key implications and scope for future research.